Dendrobium chiangdaoense (Orchidaceae), a new species from Thailand - Prommanut, Phattaravee; Kidyoo, Manit; Buddhawong, Wins; Suddee, Somran (Phytotaxa, 2017)
Dendrobium chiangdaoense, a new species belonging to Dendrobium section Stachyobium is described and illustrated. It is only known from the type locality in mixed deciduous forest at ca. 800 m elev. on limestone hills in Chiang Dao District, Chiang Mai Province, northern Thailand. It most closely resembles D. dixonianum, a more widespread northern Thailand species occurring in upper montane rain forest at 1,650–1,800 m elev.